Direct tracking of the polysulfide shuttling and interfacial evolution in all-solid-state lithium–sulfur batteries: a degradation mechanism study. Issue 8 (13th June 2019) - Song, Yue-Xian; Shi, Yang; Wan, Jing; Lang, Shuang-Yan; Hu, Xin-Cheng; Yan, Hui-Juan; Liu, Bing; Guo, Yu-Guo; Wen, Rui; Wan, Li-Jun
Abstract : In situ monitoring of the interfacial processes in working all-solid-state lithium–sulfur batteries provides deep insights into the degradation mechanisms and temperature dependence. Abstract : With a remarkably high energy density and high safety, all-solid-state lithium–sulfur (ASSLS) batteries have emerged as promising next-generation energy storage systems. Direct tracking of the structural evolution at the solid–solid interfaces in an ASSLS battery is highly significant for deep understanding of the reaction mechanism to further improve the electrochemical performance. Herein, we present in situ monitoring of the evolution processes at both the cathode/electrolyte and anode/electrolyte interfaces in working ASSLS batteries via real-time optical microscope (OM) imaging. An irreversible transformation from bright-white to dark-brown in the polymer–ceramic composite electrolyte was directly captured upon discharge/charge, which indicates a shuttling process of polysulfides in the solid-state electrolyte further supported by XPS and Raman analyses. Furthermore, the in situ visualization of the temperature dependency of structural evolution clearly reveals that temperature greatly influences the polysulfide shuttling, irreversible volume-change of solid-state electrolytes and volume expansion of Li metal, which are directly correlated with the degradation of battery performance. These results provide a deep insight into the evolution processes of both structure and component in a working ASSLS battery, which could guide one to explore the electrochemical reactions at solid–solid interfaces and failure mechanism to design high performance lithium–sulfur batteries.